Self-stigma and weight loss: The impact of fear of being stigmatized. (June 2020) - Lillis, Jason; Thomas, John G; Levin, Michael E; Wing, Rena R
This study sought to examine whether two facets of weight self-stigma (fear of enacted stigma and self-devaluation) were associated with weight change and treatment engagement for 188 individuals participating in a 3-month online weight loss program. Fear of enacted stigma predicted less weight loss 3 months later after controlling for demographics, eating problems, and psychological symptoms. Self-devaluation did not predict weight loss. Neither weight self-stigma variable predicted engagement in the online program. These results add to the literature indicating the negative effects of weight self-stigma while highlighting the central role of fear of being stigmatized by others in this process.